2001
DOI: 10.1007/s002510100319
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Clr , a new family of lectin-like genes localized between mouse Nkrp1a and Cd69

Abstract: We report the identification of a novel family of genes, named Clr, encoding C-type lectin-like molecules, which maps in the natural killer (NK) gene complex (NKC) on mouse Chromosome 6. Genomic sequence analysis indicates the presence of at least seven members between Nkrpla and Cd69. By RT-PCR, at least three members of the family are expressed on interleukin-2-activated NK cells. Sequence analysis revealed complete open reading frames of 203-205 amino acids, with a carboxyl-terminal C-type lectin-like carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
80
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 0 publications
5
80
1
Order By: Relevance
“…This implies, as suggested previously, that NKRP1D-Clr-b interactions may provide an alternative missing self-recognition system (11,12) in which disease-induced loss of protective Clr-b molecules from normal cells induces susceptibility to NK attack. Support for such a mechanism in the rat has been provided by the finding that rNKRP1C ϩ NK cells could kill syngeneic blasts in the presence of anti-NKRP1C mAb (37).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This implies, as suggested previously, that NKRP1D-Clr-b interactions may provide an alternative missing self-recognition system (11,12) in which disease-induced loss of protective Clr-b molecules from normal cells induces susceptibility to NK attack. Support for such a mechanism in the rat has been provided by the finding that rNKRP1C ϩ NK cells could kill syngeneic blasts in the presence of anti-NKRP1C mAb (37).…”
Section: Discussionmentioning
confidence: 62%
“…1), associate with SHP-1, and deliver inhibitory signals when cross-linked by mAbs or ligands (9 -12). A major breakthrough in our understanding of NKRP1 molecules was the discovery that the ligands of at least some NKRP1s belong to a family of related proteins, designated Clr proteins, encoded by genes interspersed among the Nkrp1 genes themselves (11)(12)(13). In particular, it was shown that NKRP1B/D recognizes Clr-b and that transfected cells expressing Clr-b are partially protected from lysis by NK cells, leading to the suggestion that NKRP1B/D-Clr-b recognition represents a novel form of missing-self-recognition designed to monitor cellular levels of Clr-b (11,12).…”
mentioning
confidence: 99%
“…In the C57/129 isoform, this is replaced by arginine, thereby precluding the formation of a conserved disulfide bond, found in all CRD crystal structures that have been solved, with the preceding conserved cysteine (C238 in Ly49B). The only other animal C-type lectins known to lack this conserved cysteine are the mouse Clr molecules (40) and their human ortholog LLT1 (41) that are encoded in the NKRP1 region of the NK complex and act as ligands for NKRP1 molecules (42)(43)(44)(45). In addition, several of the conserved core hydrophobic residues thought to be important for determining the basic structure of the CRD are altered in Ly49B.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NKR-P1 family has expanded to include both activating and inhibitory members in rodents, it consists of only one member in several other mammalian species, including in human [6]. The nature of their ligands has been controversial [7,8], but it has recently been shown that members of another KLR-related receptor family, the C-type lectin-related (Clr) molecules [9], also termed C-type lectin 2D (CLEC2D), can act as ligands for certain NKR-P1 molecules [10,11]. The Clr gene family also shows considerable expansion in rodents and the Clr genes are interspersed with the Nkrp1 genes in the proximal (centromeric) part of the NKC.…”
mentioning
confidence: 99%